[Advanced nursing practice: vision in Switzerland]. - Morin, D.; Ramelet, Anne-Sylvie; Shaha, M. (2013)
To meet the challenges related to the development of health problems taking into account the development of knowledge, several innovations in care are being implemented. Among these, advanced nursing roles and increased interprofessional collaboration are considered as important features in Switzerland. Although the international literature provides benchmarks for advanced roles, it was considered essential to contextualize these in order to promote their application value in Switzerland. Thus, from 79 statements drawn from the literature, 172 participants involved in a two-sequential phases study only kept 29 statements because they considered they were relevant, important and applicable in daily practice. However, it is important to point out that statements which have not been selected at this stage to describe advanced practice cannot be considered irrelevant permanently. Indeed, given the emergence of advanced practice in western Switzerland, it is possible that a statement judged not so relevant at this moment of the development of advanced practice, will be considered as such later on. The master's program in nursing embedded at the University of Lausanne and the University of Applied Sciences Western Switzerland was also examined in the light of these statements. It was concluded that all the objectives of the program are aligned with the competencies statements that were kept.